Anatomy of Global Stock Market Crashes An Empirical Analysis - Chakrabarti, Gagari; Sen, Chitrakalpa; SpringerLink (Online service) (India : Springer India, 2012)
This work is an exploration of the global market dynamics, their intrinsic natures, common trends and dynamic inter-linkages during the stock market crises over the last twelve years. The study isolates different phases of crisis and differentiates between any crisis that remains confined to the region and those that take up a global dimension. The latent structure of the global stock market, the inter-regional and intra-regional stock market dynamics around the crises are analyzed to get a complete picture of the structure of the global stock market. The study further probing into the inherent nature of the global stock market in generating crisis finds the global market to be chaotic thus making the system intrinsically unstable or at best to follow knife-edge stability. The findings have significant bearing at theoretical level and on policy decisions.
Keywords: Economics; Macroeconomics; Finance; Economics/Management Science; Financial Economics; Macroeconomics/Monetary Economics; Finance/Investment/Banking.; Economics/Management Science, general